2010
DOI: 10.1016/j.foodchem.2010.02.069
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of a soybean cultivar lacking lipoxygenases (LOX2 and LOX3)

Abstract: a b s t r a c tThe nutrient, phytic acid, oxalate, trypsin inhibitors and isoflavones composition of a whole soy flour produced from a new cultivar (UFV-116), lacking lipoxygenases 2 and 3, compared to a conventional cultivar (OCEPAR-19) were determined. Protein and dietary fibres (total, soluble and insoluble) were similar for both cultivars. OCEPAR-19 was higher in lipids and UFV-116 in ash content (p < 0.05). Indispensable, dispensable and total aminoacid as well as Ca, K and Mg were higher for UFV-116. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 25 publications
1
33
0
2
Order By: Relevance
“…It reported to improve the quantity of highly digestible soluble matters by almost three times (22 to 65%) and at the same time almost 40% total defatted dry matter becomes dialyzable due to degradation of high molecular weight compounds (Kiers et al, 2000). One of the most reported health benefits of B. subtilis fermentation is almost complete removal of indigestible oligosaccharides such as sucrose, trisaccharides (raffinose), tetrasaccharides (stachyose) which are responsible for indigestion and flatulence in humans and in monogastric animals (Sarkar and Tamang, 1995;Esteves et al, 2010). Fermentation reduces anti-nutrients level in soybeans which hinder the availability of proteins and phytochemicals.…”
Section: Health Benefits Of B Subtilis Fermented Soybeansmentioning
confidence: 99%
See 2 more Smart Citations
“…It reported to improve the quantity of highly digestible soluble matters by almost three times (22 to 65%) and at the same time almost 40% total defatted dry matter becomes dialyzable due to degradation of high molecular weight compounds (Kiers et al, 2000). One of the most reported health benefits of B. subtilis fermentation is almost complete removal of indigestible oligosaccharides such as sucrose, trisaccharides (raffinose), tetrasaccharides (stachyose) which are responsible for indigestion and flatulence in humans and in monogastric animals (Sarkar and Tamang, 1995;Esteves et al, 2010). Fermentation reduces anti-nutrients level in soybeans which hinder the availability of proteins and phytochemicals.…”
Section: Health Benefits Of B Subtilis Fermented Soybeansmentioning
confidence: 99%
“…Fermentation reduces anti-nutrients level in soybeans which hinder the availability of proteins and phytochemicals. It does help in improving the protein digestibility (Esteves et al, 2010). Shrestha and Noomhorm, (2001), found the urease activity of Kinema (dried) is close to zero and concluded that steps Kinema preparation lead to inactivation of anti-nutrients such as trypsin inhibitors and other biologically active enzymes in naturally present in raw soybeans.…”
Section: Health Benefits Of B Subtilis Fermented Soybeansmentioning
confidence: 99%
See 1 more Smart Citation
“…Phytic acid naturally occurs in most soybean products, in concentrations ranging from 1-3% (Esteves et al, 2010). But in this study the phytic acid content of SBBs varied from 1 to 3.31 mg/100 ml beverage.…”
Section: Change In Beta-carotene Contentmentioning
confidence: 57%
“…However, soybean contains lipoxygenases, related to lipid peroxidation, which causes the beany fl avor and thus restricts the consumption of legumes. To overcome this problem and increase the consumption of soybeans, lipoxygenases-free cultivars with improved fl avor are being developed (ESTEVES et al, 2011).…”
Section: Introductionmentioning
confidence: 99%